The nature of giant clumps in distant galaxies probed by the anatomy of the cosmic snake. (January 2018) - Cava, Antonio; Schaerer, Daniel; Richard, Johan; Pérez-González, Pablo; Dessauges-Zavadsky, Miroslava; Mayer, Lucio; Tamburello, Valentina
Abstract Giant stellar clumps are ubiquitous in high-redshift galaxies1, 2 . They are thought to play an important role in the build-up of galactic bulges3 and as diagnostics of star formation feedback in galactic discs4 . Hubble Space Telescope (HST) blank field imaging surveys have estimated that these clumps have masses of up to 109.5  M ⊙ and linear sizes of ≳1 kpc5, 6 . Recently, gravitational lensing has also been used to get higher spatial resolution7–9 . However, both recent lensed observations10, 11 and models12, 13 suggest that the clumps' properties may be overestimated by the limited resolution of standard imaging techniques. A definitive proof of this observational bias is nevertheless still missing. Here we investigate directly the effect of resolution on clump properties by analysing multiple gravitationally lensed images of the same galaxy at different spatial resolutions, down to 30 pc. We show that the typical mass and size of giant clumps, generally observed at ~1 kpc resolution in high-redshift galaxies, are systematically overestimated. The high spatial resolution data, only enabled by strong gravitational lensing using currently available facilities, support smaller scales of clump formation by fragmentation of the galactic gas disk via gravitational instabilities. A galaxy atz ~ 1 is multiply imaged by strong lensing with different spatial resolutions. The properties of the giant stellar clumps within the galaxy depend on the resolution of the images. This observational effect must be considered in galactic models of star formation.